MEKANISME AKSES PADA HAK KEPEMILIKAN DI KESATUAN PENGELOLAAN HUTAN PRODUKSI MERANTI, SUMATERA SELATAN - Ja Posman Napitu; Aceng Hidayat; Sambas Basuni; Sofyan Sjaf (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
The interest of various parties on forest utilization access lead to the ambiguity of property rights due to user overlapping. This research explained the ambiguity factors of property rights from access mechanism and its relation to the land conflict. The research using purposive sampling method to obtain data of land use change, documents, historical study, as well as in-depth interviews of 123 people key informant. Rapid Land Tenure Assessment (RaTA) and descriptive analysis method were used to analyze the data. The results showed that both access and property rights theory could explain the overlapping use on forest area in Meranti Forest Management Unit (FMU). Analysis of rights-based access mechanism explained factors within the property rights status and the causes of land overlapping, i.e. the dynamics of management change, boundaries area issues, and lack of control. The factors of land user based on structure mechanism were the kinship ties, patroness system or pesirah, community and religious leaders. The access of structure mechanism have lead to claim of 38.53% areas of Meranti FMU. Changes of the rules have increased new users and causing overlapping between bussines license holder with community access. The research recommends avoiding change of area management forms, and for involving local communities in determining new users, duration, and profit sharing.